Value-relevance do goodwill e de ativos intangíveis identificados em combinação de negócios: evidências no Brasil - Façanha, Magali Carvalho (2019)
Faced with the convergence to IFRS accounting standards, researchers have been empirically testing the relevance of accounting information for the capital market. Within the scope of the International Accounting Standards Board (Iasb) pronouncements, we highlight IFRS 3 - Business Combinations -, which deals with business combinations. It establishes that the acquiring companies must recognize the effects of the transaction by applying the Purchase Price Allocation (PPA) method. In this process, among other elements, the identified intangible assets and goodwill are recognized. The accounting standards claim that the allocation of the purchase price to the net assets acquired is useful for investors, considering that the informative content of this method may influence the decisions of investors regarding the allocation of capital. On the other hand, some scholars raise doubts and questions about this aspect, while others support it. Thus, this research aims to investigate whether the information provided in the purchase price allocation process, especially goodwill and identified intangible assets, over the measurement period of the business combination, are value-relevant to the Brazilian capital market. This is a descriptive study, of a quantitative nature, using documentary procedure, with a sample composed of 39 Brazilian publicly traded companies that in the triennium 2015-2017 performed business combination in the role of acquirer, making up 85 transactions. The data were extracted from the Explanatory Notes to the annual and interim financial statements and the Economatica® database. Multiple linear regression models derived from the Ohlson (1995) model were used to achieve the research objective. The results indicated that the information on the allocation of the purchase price, in particular goodwill and identified intangible assets, was not statistically significant, and, therefore, did not present a value-relevant. Furthermore, according to the evaluation of the explanatory power of the models, it is not possible to affirm that throughout the measurement period there was an informational increase of value-relevance in the disclosure of the purchase price allocation. This study gathers some contributions; it is the first in Brazil to investigate the value-relevance of information on purchase price allocation throughout the measurement period of the business combination; it highlights the opportunity for future improvement of the standard by investigating the content of the PPA explanatory notes; and the conclusions contribute with evidence to further foster debate among regulatory bodies and the academic community about the effectiveness of the standard and the utility of PPA.